Immunogenomic Phase-Based Differences in Complete Blood Count Profiles of COVID-19 Patients With and Without Comorbidities - Ratu Diva Nuralifia Yusuf; Musofa Rusli; Hartono Kahar (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2026)
Highlights: Complete blood count profile represents the most frequently conducted laboratory test, pivotal for prognostic assessment, particularly in COVID-19 patients presenting with comorbidities. Significant differences exist within CBC profiles across various immunogenomic phases, notably leukocyte count, thrombocyte count, and NLR.   Abstract Introduction: The coronavirus disease (COVID-19) pandemic has resulted in significant mortality in Indonesia, particularly affecting those with comorbidities. Utilizing complete blood count (CBC) profiles can inform clinical management strategies and enhance patient care. This study examined the correlations among CBC profiles, immunogenomic phase, and disease pathophysiology. Methods: This was a cross-sectional, retrospective, observational study using medical records from Dr. Soetomo General Academic Hospital in Surabaya, Indonesia. Demographic data from 134 COVID-19 patients were analyzed, focusing on differences in CBC profiles between patients with and without comorbidities across immunogenomic phases. Statistical comparisons were conducted using the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 13.0, with significance set at p<0.05. Results: Most patients were male, with a mean age of 52.13 years old. Cardiovascular comorbidities were prevalent (36%) across all immunogenomic phases. Significant differences in leukocyte and platelet counts were observed among patients with comorbidities. The neutrophil-to-lymphocyte (NLR) ratio varied significantly between immunogenomic phases in both comorbid and non-comorbid groups. Additionally, significant variations in leukocyte and platelet counts were found in the comorbid group, along with differences in NLR in both groups (p<0.05). Conclusion: Variations in leukocyte count, platelet count, and NLR indicated that comorbidities and CBC profiles might contribute to the development of cytokine storm, acute respiratory distress syndrome, and multiple organ failure.